Immunity to Hepatitis B is Undetectable in the Majority of Adolescents and Young Adults Seeking Outpatient Medication Treatment for Opioid Use Disorder. Issue 6 (December 2020) - Stull, Samuel W.; McKnight, Erin R.; Matson, Steven C.; Bonny, Andrea E.
Abstract : Objective: To assess prevalence and predictors of hepatitis B immune status among adolescents and young adults (AYA) seeking outpatient medication treatment for opioid use disorder (MOUD). Study Design: A retrospective medical chart review was conducted of AYA seeking MOUD between January 1, 2013 through December 31, 2015. Inclusion criteria included: diagnosis of opioid use disorder according to the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition; received hepatitis serologic testing; and no evidence of prior or current hepatitis B infection. Hepatitis B immunization initiation was defined as a record of at least 1 hepatitis B vaccination; while receipt of at least 3 vaccinations indicated immunization completion. The presence of hepatitis B surface antibody (anti-HBs) was the primary outcome measure. Results: Of the 193 patients that met eligibility criteria, the presence of anti-HBs was evident in 62 (32.1%). Hepatitis B immunization initiation and completion before presenting for MOUD was documented in 102 (52.9%) and 84 (43.5%). In multivariable logistic regression modeling, hepatitis B immunization initiation after infancy was associated with increased odds of having protective anti-HBs relative to immunization series initiation in infancy (OR 8.96, 95% CI 1.57–51.05). Completion of hepatitis B immunization series after infancy as compared to completion in infancy also increased the odds of protective anti-HBs (OR, 6.68, 95% CI 2.10–21.24). Conclusions: Rates of immunity to hepatitis B were low in AYA seeking MOUD. It is important to immunize patients seeking MOUD for hepatitis B and follow up with checks for seroconversion.